Knowledge and perception of stakeholders on ecotourism development in and around old Oyo national park, Nigeria (2017)
Ecotourism development (ED) is one of the factors promoting sustainable utilisation of natural resources. Stakeholders’ attitude towards natural resources in Old Oyo National Park (OONP) can undermine or enhance conservation goals of the park. Information on stakeholders’ knowledge and perception that can be used for ED in OONP is limited. Therefore, this study assessed the knowledge and perception of stakeholders on ED in OONP, Nigeria. Simple random sampling technique was used to select 220 residents in 27 out of 59 settlements within 20 km radius of the park. Stratified random sampling technique was used to select 95 park staff (PS) and purposive sampling technique to select 354 tourists and 125 ecotourism-related entrepreneurs; giving a total of 794 respondents. Four sets of structured questionnaire were used for the study. Information on socio-demographic characteristics (age, education, ethnicity, occupation, income, cadre, number of visit, service provided), knowledge and perception of stakeholders on ED, factors limiting ED and effectiveness of park management strategies were assessed. Indices of knowledge about ED (1-26; poor 1-12, good 13-26) and perception on ED (1-76; negative 1-75, positive 76-152) were generated. Data collection was done during on- and off-seasons of ecotourism activities in 2014 and 2015. Data were analysed using descriptive statistics, Chi-square, ANOVA and logistic regression at α0.05. Respondents’ ages were 34.8±6.3, 32.4±6.1, 26.9±7.4 and 35.7±3.8 years for residents, park staff, tourists and entrepreneurs, respectively. Residents (8.0%) and tourists (96.6%) had tertiary education. PS cadres were senior (57.9%) and junior (42.1%). Tourists (95.2%) had visited the park, twice. Entrepreneurs provided the following services: accommodation (8.0%), food (37.6%), communication-related (14.4%), souvenir (7.2%) and transportation (32.8%). Most respondents: residents (65.0%), PS (87.0%), tourists (66.0%) and entrepreneurs (74.0%) had good knowledge of ED. Fifty-five percent of residents and PS (65.0%) had negative perception of ED while most tourists (84.0%) and entrepreneurs (61.0%) had positive perception of ED. Inadequate funding was considered as a serious constraint to ED by residents (52.3%), PS (45.3%), tourists (64.7%) and entrepreneurs (56.8%). Management strategy on environmental education was rated as poor by residents (67.7%), PS (45.3%), tourists (61.3%) and entrepreneurs (63.2%). There was significant relationship between ethnicity and knowledge of residents on ED (χ2 =26.73) as well as between occupation and perception of tourists on ED (χ2 =14.83). There was significant difference between residents and PS on knowledge of ED (0.22±0.06) as well as between residents and tourists on perception of ED (0.39±0.04).Igbo residents were more likely to have good knowledge of ED than their Yoruba counterparts (OR: 2.20; CI: 1.18-4.11). Tourists with monthly income of N50,000–N99,999 were more likely to have positive perception of ED than those with monthly income of less than N50,000 (OR: 4.26; CI: 1.12-8.24). Majority of stakeholders had good knowledge of ecotourism development while only tourists and entrepreneurs had positive perception of ecotourism development. Ethnicity and monthly income affected knowledge and perception of stakeholders on ecotourism development. Under-funding hindered ecotourism development in Old Oyo National Park.